2020
DOI: 10.1111/ene.14473
|View full text |Cite
|
Sign up to set email alerts
|

Miller‐Fisher syndrome after COVID‐19: neurochemical markers as an early sign of nervous system involvement

Abstract: Miller-Fisher syndrome (MFS) is classified as a variant of Guillain-Barr e syndrome (GBS), accounting for 5%-25% of all GBS cases. Since the coronavirus disease-2019 (COVID-19) outbreak, increasing evidence has been reported of the neurological manifestations of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, affecting both the central and peripheral nervous system. Here we report the clinical course, detailed cerebrospinal fluid (CSF) profile including CSF/blood antibody status, and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 8 publications
3
65
2
3
Order By: Relevance
“…However, a possible bias might rely on the lack of systematic data concerning the latency between symptom onset and CSF sampling in COVID-19 GBS cases. On another issue, in a further case of MFS associated with-COVID-19, who came to our attention, we observed the absence of intrathecal synthesis of SARS-CoV-2 antibodies together with a massive increase of CSF phosphorylated neurofilament heavy chain (pNfH) and serum neurofilament light chain (NfL) proteins, supporting the role of neurochemical markers as easily implementable tools for the detection of nervous system affection in COVID-19-related diseases [81,82].…”
Section: Discussionsupporting
confidence: 52%
“…However, a possible bias might rely on the lack of systematic data concerning the latency between symptom onset and CSF sampling in COVID-19 GBS cases. On another issue, in a further case of MFS associated with-COVID-19, who came to our attention, we observed the absence of intrathecal synthesis of SARS-CoV-2 antibodies together with a massive increase of CSF phosphorylated neurofilament heavy chain (pNfH) and serum neurofilament light chain (NfL) proteins, supporting the role of neurochemical markers as easily implementable tools for the detection of nervous system affection in COVID-19-related diseases [81,82].…”
Section: Discussionsupporting
confidence: 52%
“…1 patient had a SARS-CoV-2 IgG and IgA:blood antibody level<1, negative oligoclonal bands and no evidence of synthesis in the Reiber diagram [ 119 ]…”
Section: Resultsmentioning
confidence: 99%
“…CSF antibodies to SARS-CoV-2 were tested in 58/414 (14%) patients who did not have a positive CSF SARS-CoV-2 PCR (49/58 (84%) of whom had symptoms that localized to the CNS and 9/58 (16%) of whom had symptoms that localized to the PNS) [ 6 , 13 , 25 , 31 , 43 , 46 , 98 , 101 , 113 , 119 , 127 , 141 , 182 , 193 , 197 , 209 , 220 , 224 , 231 , 233 , 237 , 246 ]. Of these, 42/58 (72%) tested positive for SARS-CoV-2 antibodies in the CSF [ 6 , 25 , 31 , 43 , 46 , 98 , 119 , 127 , 193 , 197 , 209 , 224 , 231 , 237 ]. Keller et al noted that the 5 patients they reported did not have intrathecal synthesis of SARS-CoV-2 IgG, but did not comment on whether any SARS-CoV-2 antibodies were present in the CSF [ 182 ].…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed all the cases excluded by Abu-Rumeileh et al also and found no positive ganglioside antibodies among those excluded patients. We have identified seven more reported individual cases, which have not been included in any case review to date [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Including our current case, there are 83 individual cases of COVID-19 related GBS or MFS being reported to date.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%